2002
DOI: 10.1590/s1517-74912002000400001
|View full text |Cite
|
Sign up to set email alerts
|

Rumos da Pesquisa Odontológica

Abstract: Des de o iní cio da dé ca da de 70, já se dis se mi na vam os con ce i tos da Ter ce i ra Onda (Tof fler), a pro pa ga da "era da in for ma ção", em vir tu de dos avan ços das te le co mu ni cações e da mí dia te le vi si va, de mons tran do que co me çá va mos a vi ver na al de ia glo bal (Mac Lu han) e anun ci an do o con ce i to de glo ba li za ção. Ape sar des ses as pec tos, as lín -guas de ori gem la ti na não pu de ram al can çar sua in ter na ci o na li za ção, como acon te ceu com o fran cês e, hoje, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…[15], after analyzing the abstracts of the BSDR Annals, from 2001 to 2006, put the collective health in the sixth position, with an evident tendency towards increasing, which according to the authors showed the great concern on not only the biological aspects but also on the context of the individuals. Other authors highlighted that this increasing in the research in collective health occurred due to the closer relation between the educational institutional and the Unified Health System, together with the great interest in social questions [2,3]. According to Narvai [20], the increasing in the number of publications on collective health is a reality, not a tendency.…”
Section: Discussionmentioning
confidence: 99%
“…[15], after analyzing the abstracts of the BSDR Annals, from 2001 to 2006, put the collective health in the sixth position, with an evident tendency towards increasing, which according to the authors showed the great concern on not only the biological aspects but also on the context of the individuals. Other authors highlighted that this increasing in the research in collective health occurred due to the closer relation between the educational institutional and the Unified Health System, together with the great interest in social questions [2,3]. According to Narvai [20], the increasing in the number of publications on collective health is a reality, not a tendency.…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados aqui descritos vão ao encontro da observação de Barros (25) e Birman (26), que afirmam que o progresso observado na saúde coletiva reflete a demanda crescente das universidades e principalmente do Sistema Único de Saúde. Embora incipiente, tal evolução quantitativa acena para uma nova realidade, na qual o interesse pelo social vem se consolidando como objeto de estudo nas instituições de ensino e pesquisa.…”
Section: Discussionunclassified
“…Randomized controlled trials, case-control studies, cohort, systematic reviews and case series corresponded to 9.2% of all published articles. due, at least in part, to the growing interest and demands for production of knowledge that contributes to the Unified Health System (SUS) [14,15]. Another important aspect is that the PBOCI is the Brazilian Journal with the largest annual publication of articles in the field of oral health in public health [16].…”
Section: Resultsmentioning
confidence: 99%